Initial Validation of the U.S. Army Global Assessment Tool. Issue 6 (6th October 2016) - Vie, Loryana L.; Scheier, Lawrence M.; Lester, Paul B.; Seligman, Martin E. P.
Abstract : The U.S. Army developed the Global Assessment Tool (GAT) to monitor psychosocial fitness and well-being among soldiers and provide a means to objectively gauge the success of newly implemented resilience training programs. Despite its widespread use (taken over 5.2 million times) and stated utility for program evaluation, there is relatively little published evidence regarding the GAT's reliability and validity. We used exploratory structural equation modeling (ESEM) with 4 random samples of soldiers ( n = 10, 000 each) to examine the factorial validity and reliability of the GAT. An 11-factor solution (Self-Management, Positive Affect, Meaning, Work Engagement, Organizational Trust, Loneliness, Negative Cognitions, Hostility, Negative Emotions, Depressive Symptoms, and Emotion-Focused Coping), with 4 additional factors assessing character strengths (Intellect, Warmth, Civic Strengths, and Temperance), fit well and replicated in a second random sample. A higher order, 2-factor model using composites scores and positing positive and negative psychosocial competencies also fit well. Tests of measurement invariance using a third random sample reinforced consistent measurement properties across gender, age, and rank, with the exception of character strengths, which produced different factor structures for males and females. Further validity tests using a fourth random sample underscored a modicum of divergence among the resilience factors and convergence among the character strengths factors. We conclude with recommendations for enhancing and refining the GAT and discuss the GAT's utility as a reliable, multidimensional psychosocial assessment that can be used to evaluate the efficacy of military resilience training programs.